Facile synthesis of few-layer MoS2 in MgAl-LDH layers for enhanced visible-light photocatalytic activity. Issue 42 (5th August 2019) - Zheng, Guoyuan; Wu, Caihong; Wang, Jilin; Mo, Shuyi; Wang, Yanwu; Zou, Zhengguang; Zhou, Bing; Long, Fei
Abstract : Few-layer MoS2 was successfully grown in MgAl-LDH layers, utilizing the "space-confining" effect. The composite completed degraded 50 mg L −1 and 100 mg L −1 methyl orange (MO) solutions in 45 min and 105 min, respectively. Abstract : A new photocatalyst, few-layer MoS2 grown in MgAl-LDH interlayers (MoS2 /MgAl-LDH), was prepared by a facile two-step hydrothermal synthesis. The structural and photocatalytic properties of the obtained material were characterized by several techniques including powder X-ray diffraction (XRD), Raman spectroscopy, field emission scanning electron microscopy (FESEM), high-resolution transmission electron microscopy (HRTEM), Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), photoluminescence spectroscopy (PL) and UV-vis absorption spectroscopy. The MoS2 /MgAl-LDH composite showed excellent photocatalytic performance for methyl orange (MO) degradation at low concentrations (50 mg L −1 and 100 mg L −1 ). Furthermore, even for a MO solution concentration as high as 200 mg L −1, this composite also presented high degradation efficiency (>84%) and mineralization efficiency (>73%) at 120 min. The results show that the MoS2 /MgAl-LDH composite has great potential for application in wastewater treatment.